Usuwanie związków biogennych ze ścieków w oczyszczalniach do 15000 RLM = Biogenic compounds removal from wastewater in wastewater treatment plant less than 15,000 population equivalent - Sadecka, Zofia; Waś, Janusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the main issues for water and sewage administration on the guidelines of the National Program of Municipal Wastewater in the context of small wastewater treatment. Attention was drawn to the necessity and possibility of nitrogen and phosphorus removal in highly efficient wastewater treatment plant in population equivalent <15 000.
Keywords: małe oczyszczalnie ścieków; azot; fosfor; small wastewater treatment plants; nitrogen in recultivation; phosphorus